Intermittent auscultation fetal monitoring practice in different UK birth settings: a cross-sectional survey - Megan Douthwaite; Alessandra Morelli; Sara Kenyon; Julia Sanders; Rachel Rowe (BMC Pregnancy and Childbirth)
Abstract Background Intrapartum fetal heart rate monitoring is used to assess fetal wellbeing throughout labour. The interpretation of fetal heart rate patterns during labour informs decisions about clinical management and intervention. The World Health Organisation and other professional health care bodies recommend intermittent auscultation (IA) for monitoring the fetal heart rate for women with uncomplicated labour. Despite this there is little research on how IA is carried out in practice. This study aimed to describe IA practice across different birth settings in the United Kingdom (UK). Methods We conducted an online cross-sectional survey between November 2022 and February 2023. The survey explored whether local guidance on IA was in place; the frequency of IA training and competency assessment and packages used; content and frequency of IA audits; access to and use of IA devices; fetal heart rate counting methods used; and use of ‘fresh ears’. We invited respondents from 205 alongside and freestanding midwifery units, and 33 obstetric units in National Health Service (NHS) organisations without midwifery units, from 140 NHS organisations across the UK. Descriptive statistics were used to analyse responses about IA practice by birth setting. Results One hundred and seventy-four units (73%) responded from 119 NHS organisations. Most (91%) had local IA guidance in place for midwifery or obstetric led care, or both. While most maternity units (58%) required midwives to undertake annual IA training and competency assessments, 18% did not. A third of units reported an annual IA audit, but 67% of units had no set frequency or did not know the timing of their unit IA audit. At least six different methods for counting the fetal heart rate were reported, with 45% using some form of ‘Intelligent IA’ counting method. Just under half of units reported implementing ’fresh ears‘ for IA. Conclusions This was the first national survey of IA practice in the UK, and provides evidence of widespread variation in practice. Further investigations would be helpful to better understand why certain practices are followed or not, and the rationale behind these decisions in a clinical setting. Evidence to inform IA best practice is urgently needed.